Laser-induced modification and formation of periodic surface structures (ripples) of amorphous GST225 phase change materials. (May 2019) - Kozyukhin, Sergey; Lazarenko, Petr; Vorobyov, Yuri; Baranchikov, Alexander; Glukhenkaya, Victoria; Smayev, Mikhail; Sherchenkov, Alexey; Sybina, Yuliya; Polohin, Alexander; Sigaev, Vladimir
Highlights: Partial crystallization of GST225 films was triggering by a ten fs-pulse number. Laser-induced periodic surface structures (ripples) were formed by fs-multipulses. Fraction of crystalline phase differs between the ridges and valleys of the ripples. The heterogeneous crystallization model explained the phase transformation in LIPSS. Abstract: In this paper, we have studied the crystallization behavior of amorphous Ge2 Sb2 Te5 thin films upon irradiation with femtosecond laser pulses. Crystalline and melt-quenched amorphous regions were produced by exposure to laser multipulses, and were characterized by the optical microscopy and by the micro-Raman spectroscopy. Using irradiation with single laser pulses of varying fluence it was verified that crystallization was not possible, requiring minimum ten pulses for triggering partial crystallization. We obtained laser-induced periodic surface structures in the form of near-subwavelength ripples of two types with different periods. It was found that the fraction of the crystalline phase is higher in the ridges of the ripples compared to the valleys. We used the model of heterogeneous crystallization for bodies with different curvatures of the boundary surface to explain the observed effect of the phase transformation in laser-induced periodic surface structures.